Propagation probability and spread rates of self-sustained smouldering fires under controlled moisture content and bulk density conditions - Prat-Guitart,N; Rein,G; Hadden,RM; Belcher,CM; Yearsley,JM (International Journal of Wildland Fire, 2016)
The consumption of large areas of peat during wildfires is due to self-sustained smouldering fronts that can remain active for weeks. We studied the effect of peat moisture content and bulk density on the horizontal propagation of smouldering fire in laboratory-scale experiments. We used milled peat with moisture contents between 25 and 250% (mass of water per mass of dry peat) and bulk densities between 50 and 150 kg m–3. An infrared camera monitored ignition, spread and extinction of each smouldering combustion front. Peats with a bulk density below 75 kg m–3 and a moisture content below 150% self-sustained smouldering propagation for more than 12 cm. Peat with a bulk density of 150 kg m–3 could self-sustain smouldering propagation up to a critical moisture content of 115%. A linear model estimated that increasing both moisture content and bulk density significantly reduced the median fire spread rate (which ranged between 1 and 5 cm h–1). Moisture content had a stronger effect size on the spread rate than bulk density. However, the effect of bulk density on spread rate depends upon the moisture content, with the largest effect of bulk density at low moisture contents.